Understanding building failures and limit state design - Mohd. Zaid Yusof (Penerbit Universiti Sains Malaysia, 2014)
Normally structural failure results from problems at a structural (substructures or superstructures) level or in engineering term called as at the ultimate limit state (ULS). Factors that contribute to the problems including structural design problem, unexpected internal or external loads, unexpected types of vibration, material constitutive laws, theory constraint, geometrical or initial imperfection. In addition to the ULS, structural failure also due to the serviceability limit state (SLS) gone beyond limit such excessive deflection, severe structural crack or durability problem. Therefore, the skill or ability of an engineer or technologist to verify types or the nature of the problem(s) is important in building or structural investigation. However, not all problems related to the structure can be referred to the code of practice, text book or classroom experience since some problems require experience in design, site or even experience in computational modeling using finite element simulation software such as LUSAS, ABAQUS, ANSYS, etc. In addition, structural failure also can influence led economic, stability or integrity of organization or will impact on politics if not properly control or channeled. This book is not only intended for students of building, civil/structure engineering but also for building pathologists, concrete technologists, structural forensics as well as engineers involved in structural investigation.